Odpowiedzi

Najlepsza Odpowiedź!
2010-02-03T16:44:58+01:00
1.(3x-2)(4x+5)= 12x²+15x-8x-10 = 12x² + 7x - 10

2.(-2x+4)(6x-8) = -12x² +16x +24x -32 = -12x² + 40x -32

3.(2x-3)(x²-3x+7) = 2x³ -6x² +14x -3x² + 9x -21 = 2x³ - 9x²+ 23x - 21

4.(4x+3)(-2x²-3x+1) = -8x³ - 12x² +4x - 6x² -9x +3 = -8x³ -18x²-5x+3

5.(3x-5)(4x+2)+(3-x)(x+4) = 12x² +6x -20x -10 + 3x +12 -x² -4x = 11x² -15x +2

6.(9x+2)(-3x+1)+(-2x-3)(x+1) = -27x² + 9x -6x + 2 - 2x² - 2x - 3x - 3 =
= -29x² -2x -1

7.(½x-3)(2x-5) = x² - 2½x - 6x + 15 = x² - 8½x + 15

8.(¾x-2)(½x-¼)= ⅜x² - 3/16x -x + ½ = ⅜x² - 19/16x + ½

9.(½x-3)(x²-1½x-2) = ½x³ - ¾x² - 3x² -x + 4½x +6 = ½x³ - 3¾x² + 3½x +6

10.(¾x-½)(x²-2x+8) = ¾x³ -1½x² - ½x² +6x +x -4 = ¾x³ -2x² +7x -4
1 5 1